Investigate the Relationship between Institutional Ownership in Tehran Stock Exchange - Pourhosein, Mohammad Reza; Kol, Ahmad Aghazadeh Kama; Vishkaii, Bahram Molaheidari; Jourshari, Fatemeh Pouraskari (International Journal of Economics and Financial Issues, 2017)
In this research the relationship between institutional ownership and profit sharing policy with price efficiency and fluctuation in Tehran’s stock exchange is studied. Data extraction is done by Rahavard-Novin software and research data analyze is also done by E-views software. research result indicates that there is a significant relationship between institutional ownership and stock price fluctuation in accepted firms at Tehran’s stock exchange is approved and the main hypothesis is rejected, and there is a significant relationship between institutional ownership and stock returns in accepted firms at Tehran’s stock exchange is approved and the main hypothesis is rejected and also the existence of a significant relationship between institutional ownership and profit sharing returns in accepted firms at Tehran’s stock exchange is rejected and the main hypothesis is approved. Keywords: Institutional Ownership, Shared Dividend Policy, Stock Return, Stock Price Volatility JEL Classifications: E44, G23